Radiation Induced Thyroid Gland Changes in Nasopharyngeal Carcinoma Patient after Chemoradiotherapy in DR Sardjito Public Hospital - Indrasari, Sagung Rai; Solikin, .; van Diessen, Judi N.A.; Khoiria, Anisa Haqul (Asian Pacific Journal of Cancer Care, 2024)
Objective: The objective of this study was to determine the volumetric change in thyroid gland in nasopharyngeal carcinoma patients after undergoing chemoradiotherapy that could alter thyroid gland function. Furthermore, this study correlates the mean dose effect towards the decrease in thyroid volume to predict the outcoming clinical signs of radiation induced hypothyroidism (RHT). Methods: This study consists of a cross sectional retrospective evaluation of multiplanar image that comprised three planes of axial, coronal, and sagittal of all NPC patients who underwent chemoradiotherapy and received a computed tomography (CT) imaging before and three months after completing treatment to the evaluate the alteration of thyroid volume. Result: A significant decreased in thyroid volume between pre and 3 months post chemoradiotherapy was obtained in the result with p value < 0.001, along with the mean dose of 58 Gray effect towards the decreased thyroid volume with p value = 0.005. Conclusion: Our study demonstrated that reduction in thyroid volume may be seen as early as 3 months after chemoradiotherapy in nasopharyngeal carcinoma that correlates with mean dose effect towards the thyroid volume. This volume changes also accompanied by the alleviation of free T3 and free T4 before and after chemoradiotherapy. Therefore, efforts should be made to do an early evaluation of radiation induced hypothyroidism (RHT). Early treatment and additional evaluation might be considered to enhanced the quality of life of the nasopharyngeal carcinoma patient. Highlights/Key points: Significant decreased in thyroid volume and its function among NPC patients evaluated by CT imaging and thyroid panel. Correlation of the mean dose volume effect towards the decrease in thyroid volume. Prediction of the outcoming clinical signs of radiation-induced hypothyroidism in NPC patients after chemoradiotherapy.